New Ideas on the Design of the Web-Based Learning System Oriented to Problem Solving From the Perspective of Question Chain and Learning Community - Zhang, Yin; Chu, Samuel K. W. (International Review of Research in Open and Distributed Learning, 2016)
In recent years, a number of models concerning problem solving systems have been put forward. However, many of them stress on technology and neglect the research of problem solving itself, especially the learning mechanism related to problem solving. In this paper, we analyze the learning mechanism of problem solving, and propose that when designing Web-based problem solving systems, more attention should be paid to the learning mechanism involved in the problem solving process than to the technology itself. On the basis of that, some new ideas on the design of the problem solving systems are put forward in order to promote the rapid development of the Web-based problem solving systems.